Evaluating and assessing for learning - Harris, Duncan; Bell. Chris (London. : Kogan page, 1986)
Lists more than 1500 institutions of higher education and other organizations involved in the field of educational and training technology. Each entry contains information on areas of interest, current and future projects and publications. It is indexed by key word and institution
Includes bibliography and index.
Keywords: Teaching; Academic achievement; Educational evaluation; Teacher-student relationships; Educational accountability; Education Assessment